LENGTH WEIGHT RELATIONSHIP AND BIOMETRIC STUDY ON THREE SPECIES OF SCIAENIDS FROM BOMBAY WATERS - CHAKRABORTY, SUSHANT KUMAR (Journal of Indian Fisheries Association, 2015)
The length-weight relationship and Â·biometric study of three species of sciacnids viz.Otolithes cuvieri, Jolmieops vog/eri and Johnius macrorhynus arc rcJwrte